2006
DOI: 10.1083/jcb.200608073
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-mediated coupling of endoplasmic reticulum and mitochondrial Ca2+ channels

Abstract: The voltage-dependent anion channel (VDAC) of the outer mitochondrial membrane mediates metabolic flow, Ca2+, and cell death signaling between the endoplasmic reticulum (ER) and mitochondrial networks. We demonstrate that VDAC1 is physically linked to the endoplasmic reticulum Ca2+-release channel inositol 1,4,5-trisphosphate receptor (IP3R) through the molecular chaperone glucose-regulated protein 75 (grp75). Functional interaction between the channels was shown by the recombinant expression of the ligand-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

34
1,013
2
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,176 publications
(1,057 citation statements)
references
References 67 publications
34
1,013
2
8
Order By: Relevance
“…21,30,31 Our results show that GSK3β preferentially interacts with IP 3 R1, and can also interacts with IP 3 R2 and IP 3 R3 in cardiac cells (data not shown). In summary, we propose that inhibition of GSK3β might decrease the phosphorylation and the activity of IP 3 R, thereby limiting cytosolic and mitochondrial Ca 2+ overload, possibly contributing to the reduction of both cell death and infarct size at reperfusion.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…21,30,31 Our results show that GSK3β preferentially interacts with IP 3 R1, and can also interacts with IP 3 R2 and IP 3 R3 in cardiac cells (data not shown). In summary, we propose that inhibition of GSK3β might decrease the phosphorylation and the activity of IP 3 R, thereby limiting cytosolic and mitochondrial Ca 2+ overload, possibly contributing to the reduction of both cell death and infarct size at reperfusion.…”
Section: Discussionmentioning
confidence: 68%
“…19,20 Ca 2+ -handling proteins of ER and mitochondria are highly concentrated at mitochondria-associated ER membranes (MAMs), providing a direct and proper mitochondrial Ca 2+ signaling, including VDAC, Grp75 and IP 3 R1. [20][21][22] Here, we provide evidence that, following IR, a fraction of cellular GSK3β is localized at the SR/ER and MAMs. At the MAMs interface, GSK3β can specifically interact and regulate the protein composition of the IP 3 R Ca 2+ channeling complex and modulate Ca 2+ transfer between SR/ER and mitochondria.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Notably, in response to ArA, we observed a remarkable increase of VDAC at MAMs, according to previous studies demonstrating that under apoptosis-inducing conditions a narrowing of the ER-mitochondria associations occurs, and this is an important step in the execution of some apoptotic mechanisms. [26][27][28][29] To investigate a possible mechanism for ER-PTEN action, we looked for a physical interaction between PTEN and IP3R3, as release of the ER Ca 2 þ through IP3R3 appears to sensitize cells to apoptotic stimuli. 24,30 We performed co-immunoprecipitation experiments of proteins extracted from the ER fraction in basal condition or after ArA treatment, and found that PTEN co-immunoprecipitated with IP3R3, together with Akt, a known iteractor and modulator of IP3R-mediated Ca 2 þ release from the ER.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were reconstituted with coelenterazine n, following ER Ca 2 þ depletion in a solution containing 0 [Ca 2 þ ], 600 mM EGTA, 1 mM ionomycin, for 1 h at 41C, as previously described. 35 Following reconstitution, cells were washed with KRB (Krebs-Ringer modified buffer: 135 mM NaCl, 5 mM KCl, 1 mM MgSO 4 , 0.4 mM K 2 HPO 4 , 5.5 mM glucose, 20 mM HEPES, pH ¼ 7.4) containing 1 mM EGTA and 2% BSA, and transferred to the perfusion chamber. Light signal was collected in a purpose-built luminometer and calibrated into [Ca 2 þ ] values as previously described.…”
Section: Resultsmentioning
confidence: 99%